2015
DOI: 10.1016/j.abrep.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of alcohol use in the general population of Togo

Abstract: IntroductionAlcohol use is responsible for a high level of mortality and morbidity throughout the world. The WHO global strategy recommends that the detrimental effects of alcohol use be reduced.AimsThe objective of this paper was to investigate, using data from the 2010 Togo STEPS survey, alcohol use and other health-related factors in the general population of Togo.MethodsThis epidemiological investigation using the STEPwise approach was undertaken from December 1st, 2010, to January 23rd, 2011, throughout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
6
8
0
Order By: Relevance
“…Our findings are in line with those of Gureje et al [ 9 ], studies conducted in primary care settings in Nigeria [ 13 ], as well as in community [ 10 ]. These findings are also consistent with alcohol surveys conducted in Togo, a neighbouring country [ 11 ], as well as previous studies in Nigeria [ 14 ]. In consonance with our study, Grittner and colleagues [ 15 ] opined that people with lower socioeconomic status (SES) could be more vulnerable to problems related to alcohol consumption.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in line with those of Gureje et al [ 9 ], studies conducted in primary care settings in Nigeria [ 13 ], as well as in community [ 10 ]. These findings are also consistent with alcohol surveys conducted in Togo, a neighbouring country [ 11 ], as well as previous studies in Nigeria [ 14 ]. In consonance with our study, Grittner and colleagues [ 15 ] opined that people with lower socioeconomic status (SES) could be more vulnerable to problems related to alcohol consumption.…”
Section: Discussionsupporting
confidence: 92%
“…It could also be a reflection of increase in alcohol consumption over time. Our self-reported lifetime and current uses are lower than lifetime alcohol use (66.6%) and current use (62.2%) from a study in Togo, a neighbouring country [ 11 ]. This could be because the Permanent Mandates Commission of the League of Nations could not effectively check France and the European companies operating in Togo, from importing liquor to the country because of the recognized economic gains from liquor trade for the economy of France and other European countries [ 12 ].…”
Section: Discussionmentioning
confidence: 81%
“…In agreement with previous studies [6,7,[11][12][13][14][15][16][17], this study found that male sex increased the odds and older age (50-69 years) decreased the odds of engaging in HED. Sex specific role expectations and norms, such as associating drinking alcohol with masculinity, may be related to the male preponderance of HED [6,14].…”
Section: Discussionsupporting
confidence: 93%
“…"Ecuador's high poverty and income inequality most affect indigenous, mixed race, and rural populations." [10] Factors associated with HED may include male sex [6,7,[11][12][13][14][15], middle adulthood [7,16,17], specific ethnic groups [7,17,18], lower socioeconomic status [5,17,[19][20][21], urban residence [17], rural residence [6], former and current tobacco use [6][7][8]12,17,22], overweight/obesity [23][24][25], sedentary behaviour [5], physical activity [26][27][28], inadequate fruit and vegetable consumption [29], and less frequent primary health care utilization [30,31]. Epidemiological population-based surveys are needed to target interventions to prevent HED.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalences as high as 63% to 78.4% have been reported among undergraduates [12] [13]. Studies from other West African countries showed a self-reported current use of alcohol 62.2% [15].…”
Section: Introductionmentioning
confidence: 99%